1974
DOI: 10.1113/jphysiol.1974.sp010503
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial receptors and the antidiuretic hormone

Abstract: SUMMARY1. Stimulation of left atrial receptors by distending balloons located at the junction between the pulmonary veins and the left atrium and in the body of the left atrium resulted in a diuresis in anaesthetized dogs.2. In the same dogs the diuresis was not consistently associated with a reduction in the antidiuretic activity of plasma as compared with that during the initial control period. The antidiuretic activity of dog plasma was assayed in water-loaded rats anaesthetized with ethanol.3. Intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Thoren (1979) suggested that the atrial receptors attached to non-myelinated fibres in the vagi might be responsible for the reflex decrease in plasma vasopressin. His argument was based on the observation that distension of a large balloon in the lumen of the left atrium, which stimulates receptors attached to both myelinated and non-myelinated vagal afferent fibres, causes a decrease in plasma vasopressin (de Torrente, Robertson, McDonald & Schrier, 1975), whereas distension of the small balloons in the pulmonary vein -atrial junctions (Kappagoda et al 1974), stimulating predominantly receptors attached to myelinated fibres, did not cause a decrease in the antidiuretic activity of the plasma. The results of the present study do not support the above hypothesis that the atrial receptors attached to non-myelinated afferent vagal fibres are responsible for the decrease in plasma vasopressin.…”
Section: Resultsmentioning
confidence: 99%
“…Thoren (1979) suggested that the atrial receptors attached to non-myelinated fibres in the vagi might be responsible for the reflex decrease in plasma vasopressin. His argument was based on the observation that distension of a large balloon in the lumen of the left atrium, which stimulates receptors attached to both myelinated and non-myelinated vagal afferent fibres, causes a decrease in plasma vasopressin (de Torrente, Robertson, McDonald & Schrier, 1975), whereas distension of the small balloons in the pulmonary vein -atrial junctions (Kappagoda et al 1974), stimulating predominantly receptors attached to myelinated fibres, did not cause a decrease in the antidiuretic activity of the plasma. The results of the present study do not support the above hypothesis that the atrial receptors attached to non-myelinated afferent vagal fibres are responsible for the decrease in plasma vasopressin.…”
Section: Resultsmentioning
confidence: 99%
“…not significant (Student's two-tailed, paired t test). fact that plasma obtained during the period of stimulation of atrial receptors did not inhibit urine flow in the water loaded ethanol anaesthetized rat (Kappagoda et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this reflex appears to be mechanoreceptors situated in the cardiopulmonary area activating the vagal and/or sympathetic afferent fibers to control renal function. Although increases in renal excretory function have been repeatedly demonstrated by mechanical stretch of the atria (Lydtin and Hamilton, 1964;Linden, 1973;Goetz et al, 1975;Fater et al, 1982;Schultz et al, 1982), distention of the left atrium by balloon inflation (Ledsome et al, 1961;Kappagoda et al, 1974;Zehr et al, 1976), and volume expansion (Gilmore and Weisfeldt, 1965;Fater et al, 1982), it remains controversial whether the responses of renal function are mediated by vagal afferents. For example, Gilmore and Weisfeldt (1965) failed to demonstrate any difference in the natriuretic response of the kidney to acute volume expansion before and after bilateral vagotomy in the anesthetized dog.…”
Section: Discussionmentioning
confidence: 99%